Stimulation of seeds by low frequency electromagnetic field on some properties of soybean - Bajagić, Marija (Journal of Agricultural Sciences (Belgrade), 2021)
The development of science and technology leads to the creation of new approaches in crop breeding and various methods to encourage increased plant productivity. One of the latest methods is the implementation of an environmentally acceptable technique of using a pulsed low frequency electromagnetic field (PEMP). The paper presents the results of the influence of electromagnetic stimulation of soybean seeds on the number of grains per plant, weight of 1000 grains and grain yield in different agroecological conditions. Soybeans occupy an important place in terms of human and animal nutrition, because soybean seeds are rich in oil, protein and fat. In a three-year study in the period from 2013-2015, the soybean variety Valjevka was used, grown with different amounts of organic granular poultry fertilizer formulation 4: 4: 4 (control - without fertilization, 750 kg.ha-1 i 1300 kg.ha-1). Before sowing, the seeds have been subjected to the stimulation of low frequency electromagnetic field (PEMF) in the following configurations: control - without stimulation and stimulation alternating magnetic field (PEMF) with the induction of 30 mT and exposure time of 15 min. It was found that the variability of the examined parameters depended on all three factors at a statistically significant level of 1%. At the same time, the values of the examined parameters were the highest in 2014 in relation to 2013 and 2015 (except for the mass of grain per plant, which was the highest in 2013) during fertilization of 1300 kg.ha-1 and stimulation of seeds with PEMP. The average number of grains during seed stimulation was 32.64% (77.82) higher than without PEMP (58.67). The weight of 1000 grains with PEMP was 155.99 g, which was 2.06% more than the variant without PEMP (152.83 g). The average yield of soybean grain for all three years of research with seed stimulation was 4.85% (3481.25 kg.ha-1) higher than without PEMP (3320,14 kg.ha-1). Stimulation of seeds with PEMP has economic justification, given the growth of soybean prices on the world stock market. The results suggest that PEMP treatment of soybean seeds has the potential in quality, safe and high-yield production and to counteract the adverse effects such as drought and the lack of fertilizer.